PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN SEJARAH DI SMA SANTA MARIA PEKANBARU - Sarumaha, Margaretha Taniria; Tugiman, Tugiman; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Santa Maria Pekanbaru High School is a public private high school based on Catholic education, with ownership status by the Prayoga Riau Foundation which was established on October 15, 1985 with an establishment decision 18678 / I09.7d / I3-85. This research aims (1) to determine the effect of students' perceptions about teacher competence, namely pedagogical, personal, social and professional competencies on the motivation of students of Class X in history in SMA Santa Maria Pekanbaru and (2) to find out how much influence the perceptions of students about teacher competence that is pedagogical, personal, social and professional towards Class X learning motivation in the history course at Santa Maria High Pekanbaru School. The research approach used in this research is quantitative research. Using stepwise multiple linear regression analysis. The independent variable is the perception of students about the competence of the teacher (paedophile competence, personality, professional and social) and the dependent variable is the learning motivation of the student. The results obtained show that, via the t-test (partial) student perceptions of the teacher's competence on the student's learning motivation, there is a positive and significant effect when pedagogical competency rcount is 0.872 with a significance of 0,000 and non-standardized coefficients of 0.263, the personality competency of rcount is 0.853 with a significance of 0.000 and non-standardized coefficients is 0.216, social competence rcount is 0.886 with a 0,000 and non-standardised coefficients is 1,097. But for professional competencies included in the variables issued in the stepwise method, because the values in this method are positive and significant, while rcount of professional competencies is -0.093 with a significant ness of 0.211. This means that professional competence does not have a positive effect on student motivation. The positive and significant effect as a whole, shown by the F count, is 156,02 7 with a significant (P value) of 0.000. 95% (Î± = 0.05). The significance value of P (value) of 0.000 <0.05 with R squared after the multiple linear regression analysis of the stepwise method of 0.867 shows that 86.7% of the contribution of the independent variable pedagogical competence, personality competence and social competence is with regard to learning motivation variables.Key Words: Influence Of Students' Perception About Teacher Competence Against StudentMotivation In Sma Santa Maria Pekanbaru